Incidence and clinical significance of iliac vein compression. (August 2015) - Nazzal, M; El-Fedaly, M; Kazan, V; Qu, W; Renno, AW; Al-Natour, M; Abbas, J
Objectives: To determine the frequency of left common iliac vein (CIV) compression by the right common iliac artery (CIA) based on CT scan images. Methods: CT scan images were reviewed and the diameter of CIV was measured at the area of minimal diameter and compared to the distal adjacent segment and the contralateral CIV at the same level. Medical records were reviewed for symptoms, deep vein thrombosis (DVT) and risk factors that might be associated with DVT. Data were analyzed with SPSS program using both Chi square and t test. A p  < 0.05 was considered statistically significant. Linear regression (R2) was used to evaluate correlation. Results: A total of 300 complete records were reviewed. The mean age was 51.89 years, with 126 (42%) males. Comparison between the two groups (>70% vs <70%) showed similar clinical factors such as history of DVT, surgery, immobilization, malignancy, limb trauma, pregnancy, obesity, CHF, and smoking. There were more females with CIV compression of 70% or more than males (19.5% vs 11.1% P  < .049). Conclusion: Diameter stenosis more than 70% was present in 30.6% of cases with higher incidence in females. The presence of stenosis was not associated with the presence of clinical symptoms.